2019
DOI: 10.1088/1361-6528/ab11b7
|View full text |Cite
|
Sign up to set email alerts
|

Ag nanowire-based transparent stretchable tactile sensor recognizing strain directions and pressure

Abstract: In the last decade, extensive studies have been conducted to realize the functions of human skin based on stretchable electronics. An artificial skin, recognizing complex mechanical stimulation including pressure, strain and shear, and composed of transparent material, is an essential goal but has hardly been achieved. We fabricated a transparent integrated sensor system that can sense the strain direction and normal pressure of applied mechanical stimulation. Each sensor is composed of micropatterned Ag nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Silver nanowires (AgNWs), with their excellent conductivity and high anticorrosion properties, are the most intently studied among MeNWs. They remain at the forefront of TSC research as they have demonstrated their versatility in various fabrication techniques 41,43,48,62–66. Araki et al used laser induced forward transfer (LIFT), a noncontact printing technique, to make a prestrained electrode that stretched to 100% with a change of only 1.6 times the initial resistance 62.…”
Section: Materials For Tscs Based On Nanomaterialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Silver nanowires (AgNWs), with their excellent conductivity and high anticorrosion properties, are the most intently studied among MeNWs. They remain at the forefront of TSC research as they have demonstrated their versatility in various fabrication techniques 41,43,48,62–66. Araki et al used laser induced forward transfer (LIFT), a noncontact printing technique, to make a prestrained electrode that stretched to 100% with a change of only 1.6 times the initial resistance 62.…”
Section: Materials For Tscs Based On Nanomaterialsmentioning
confidence: 99%
“…Since particles in the spray are very small and evaporation during spraying occurs almost simultaneously, results of the coating are not commonly affected by fluidic effects such as Marangoni flow. In fabrication of TSCs, this method typically is used to coat 1D nanomaterials like CNT69 and MeNWs 64,66,69,73…”
Section: Fabrication Techniquementioning
confidence: 99%
See 3 more Smart Citations